Technology Dissemination of Smart Tani Fish Farmers in Karang Kepanjen Hamlet, Trimulyo Village, Sleman District, Sleman Regency - Iswanto Suwarno; Nia Maharani Raharja; Dhiya Uddin Rijalusalam; Rachmad Andri Atmoko; Irfan Ahmad; Israa Al_barazanchi; Sashikala Mishra (Peneliti Teknologi Teknik Indonesia, 2021)
Smartani